Development of Audiovisual Media of Chanting Asmaul Husna on Early Childhood Memory Ability - Wulandari, Wulandari; Sumarni, Sri; Chotimah, Umi; Syarifuddin, Syarifuddin; Yanzi, Hermi; Raharjo, Makmum (Teknodika, 2024)
Development of learning video for chanting of Al Asma Al Husna on the memory abilities of young children which this research aims to produce audiovisual media for chanting Asmaul Husna for kindergarten children that is valid, practical and effective. The development model used is the 4D development model consisting of the stages of definition, design, development and disseminate. The development stage have to more steps include namely expert validation, one to one, small group, and field test. The results show that the validity of the material is 90%, the validity of the material is 88% and the validity of the language is 91%, for the rekapitulation about expert validation is 90% in the valid category. Meanwhile, the score for one to one practicality was 68% in the practical category, and at the small group stage it was 89% in the very practical category. Meanwhile, to see the effectiveness of the media, the initial test was 87.2% and the final test was 97.8% and showed student learning outcomes which were categorized as moderate with an n-gain value of 0.63. Thus, learning of video for chanting of Al Asma Al Husna can be applied to improve the memory abilities of young children include for the children in kindergarden.